2006
DOI: 10.1111/j.1467-839x.2006.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐oriented and socially oriented cultural conceptions of subjective well‐being: Conceptual analysis and scale development

Abstract: Adopting a ‘cross‐cultural indigenous approach’ (CCI), we attempted a conceptual analysis of cultural conceptions of SWB in terms of individual‐oriented SWB (ISWB) and socially oriented SWB (SSWB) views. Also incorporating findings from our previous qualitative studies, a culturally balanced and fair measurement, The Individual‐oriented and Socially oriented cultural conceptions of SWB Scales (ISSWB) was developed and evaluated in two studies involving Chinese and American participants. The 51‐item version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 37 publications
6
75
0
5
Order By: Relevance
“…For instance, Lu and Gilmour (2006) found that their Chinese participants were more sociallyoriented (emphasizing the effect of others and the importance of fulfilling social duties) in their understanding of happiness than the Americans, whereas the Americans were more individually oriented. For example, Americans endorsed more strongly the beliefs that happiness is a born right, that happiness is personal successes, and that happiness should be actively pursued.…”
Section: Empirical Evidencementioning
confidence: 99%
“…For instance, Lu and Gilmour (2006) found that their Chinese participants were more sociallyoriented (emphasizing the effect of others and the importance of fulfilling social duties) in their understanding of happiness than the Americans, whereas the Americans were more individually oriented. For example, Americans endorsed more strongly the beliefs that happiness is a born right, that happiness is personal successes, and that happiness should be actively pursued.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Вполне очевидно то, что различные культурные ориентации задают соответствующий вектор в оценке своей жизни и своего места в ней. Так, в результате исследований Л. Лу и Р. Гилмор сделан вывод о том, что китайцы обладают более социально ориентированным благополучием, а американцы -индивидуально ориентированным [16]. В наших исследованиях было показано, что у русских психологическое благополучие обусловливается культурной характеристикой «горизонтальный индивидуализм», у казахов -«горизонтальный коллективизм», наиболее вы-раженными в соответствующих выборках [1].…”
Section: психология социального развитияunclassified
“…Striving for personal happiness and the recognition of such striving (personal accountability and explicit pursuit) are the defining features of individual-oriented cultural conceptions of SWB, whereas role obligations and dialectical reservation (role obligations and dialectical balance) are the defining features of social-oriented cultural conceptions of SWB. Subsequent research (Lu & Gilmour, 2006) verified that Chinese both in Taiwan and mainland China endorsed individual-oriented and social-oriented cultural conceptions of SWB with nearly equal strengths. However, Chinese still endorsed stronger socialoriented SWB than Americans, while Americans endorsed stronger individual-oriented SWB than Chinese.…”
Section: East Asian Social-oriented Cultural Conceptions Of Swbmentioning
confidence: 99%